HUBUNGAN PEMBESARAN PROSTAT JINAK PADA SONOGRAFI TRANSABDOMINAL DENGAN DERAJAT SUMBATAN LEHER KANDUNG KEMIH PADA UROFLOWMETRI - , Raden Bagus Adiwinoto Dwi Juwono, dr. Lina Choridah,Sp.Rad (K). ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Benign prostate enlargement, or better known as benign prostatic hyperplasia (BPH) is often found in older men, although rarely life threatening, BPH complainant that interferes with daily activities. State as a result of the enlarged prostate gland or benign prostate enlargement that causes obstruction in the bladder neck and urethra, or known as bladder outlet obstruction. Specific blockage caused by enlarged prostate gland known as benign prostatic obstruction. This study aims to determine the relationship of benign prostatic hyperplasia on transabdominal sonographic examination of the degree of bladder outlet obstruction on uroflowmetry examination. This study was observational analytic study. Sampling is done with consecutive sampling method. The sample in this study were male patients with BPH and non BPH as controls conducted examination of the prostate volume with transabdominal sonographic examination and uroflowmetry that come to Ultrasound room of Radiology Installation and Urology Clinic of Dr. Sardjito hospital. Statistical analysis was used to know differences in outcomes of uroflowmetry of the BPH group and non BPH group is t test. P-value <0.05 indicates significant differences uroflowmetry results of clinical BPH group with non BPH group, is having a significant negative relationship to the uroflometry result. To determine the relationship between BPH with the results of uroflowmetry, statistical analysis was performed is Pearson.